The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s0004-27492002000100013
|View full text |Cite
|
Sign up to set email alerts
|

Interesse e conhecimento em cirurgia refrativa entre estudantes de medicina

Abstract: Objetivo: Realizou-se um estudo em estudantes da Faculdade de Medicina do ABC a fim de analisar e relacionar a freqüência de usuários de correção óptica, o tipo de vícios de refração, o número de pessoas submetidas à cirurgia refrativa e o conhecimento e interesse por essa operação. Métodos: realizou-se um levantamento entre estudantes de medicina da Faculdade de Medicina do ABC, no período de 19 a 21 de junho de 2000. Foi utilizado um questionário auto-aplicável como instrumento de coleta de dados. Resultados… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
2
0
0
Order By: Relevance
“…We found that 92.1% of the participants had awareness of the refractive correction surgeries. This percentage of awareness resembled studies done among students in medical schools in India (92.51%) [ 34 ] and Brazil (92.8%) [ 35 ]. This result was expected since our participants were medical students and refractive surgery is a common procedure.…”
Section: Discussionsupporting
confidence: 82%
“…We found that 92.1% of the participants had awareness of the refractive correction surgeries. This percentage of awareness resembled studies done among students in medical schools in India (92.51%) [ 34 ] and Brazil (92.8%) [ 35 ]. This result was expected since our participants were medical students and refractive surgery is a common procedure.…”
Section: Discussionsupporting
confidence: 82%
“…[11,12] 86% were aware of corneal refractive surgery. This awareness rate is similar to the awareness rate in studies conducted among undergraduates in Saudi Arabia 92.1%, 92.5% in India [13], and 92.8% in Brazil [14]. However, about 38.4% of the students in our study were willing to undergo corneal refractive surgery which is similar to the study in India at 36.6%, and less than the rate of readiness of undergraduate students in Saudi Arabia for the surgery at 69.5%.…”
Section: Discussionsupporting
confidence: 85%